Intracranial metastasis in submandibular adenocarcinoma - Legaza, Elena Sánchez (2014)
Submandibular gland malignant neoplasms are rare and their intracranial metastases are exceptional, it only occurs in submandibular adenocarcinoma. Its silent symptomatology favors its regional spread, explaining thus its late diagnosis. Its prognosis depends on the histological grade, clinical staging and adequate surgical excision. Its treatment is multidisciplinary: surgery, radiotherapy and chemotherapy.